دراسة سببية للاختلاجات عند الأطفال - نداف شهيرة (Tishreen University Journal -Medical Sciences Series, 2019)
أجريت الدراسة بشكل راجع على الأطفال المقبولين في مشفى الأسد الجامعي باللاذقية – قسم الأطفال بتشخيص اختلاج من عمر شهر حتى 15 سنة مدة الدراسة عام كامل (من1/1/2004 – 31/12/2004) بلغ عدد الحالات 77 حالة لم يكن هناك فرق بين إصابة الذكور والإناث معظم الحالات كانت (89.62%) دون سن السادسة من العمر. الترفع الحروري كان أكثر أسباب الاختلاج (اختلاج حروري) 64.38% تلاه الصرع بنسبة 16.43% ثم الآفات الدماغية 9.58%. This is a retrospective study of children aged one month to 15 years who were hospitalized at Alassad hospital with primary diagnosis of convulsion during the year 2004 (1/1/2004- 12/31/2004). 77 patients were involved in this study. There were no differences between the males and the females. Most of the patients (89.62 %) were less than 6 years of age. This study demonstrates that fever is the most common cause of convulsion (64.38 % of cases), followed by epilepsy as the second cause of convulsion (16.43 % of cases), and brain lesions as the third cause of convulsion (9.58 % of cases).